Heavy metals contents in higher aquatic plants of Belarusian reservoirs and rivers: spatial and species features - Zhukovskaya, Natalia V.; Vlasov, Boris P.; Kavalchyk, Nadzeya V. (Journal of the Belarusian State University. Geography and Geology, 2019)
The spatial and species features of heavy metals (Ti, V, Cr, Mn, Ni, Cu, Zn, Zr, Mo, Pb) contents in higher aquatic plants of reservoirs and rivers within Belarus have been analyzed on monitoring data. The group of submerged plants are characterized by high ash content; and they accumulate large amounts of Ti, Mn, Cu, Zn, Zr, Pb. There are statistically signi ficant differences between the plants in ecological groups of reservoirs and rivers in terms of Mn, Cu, Pb contents in the tissues (elements with a 100 % frequency). According to the spatial analysis the reservoirs of the northern geochemical province account for 71 % of the Mn anomalies and 80 % of the Cu anomalies, including the Braslav region – 46 % of the Mn anomalies and 59 % of Cu. Mn, Cu, Pb maximum concentrations are characteristics of submerged macrophytes such lakes as Snudy, Losvido, Maloye Beloye, Beloye (Luninets District), Beloe (Surmino), Svityaz. Among submerged macrophytes within lakes the abnormal accumulation of Mn has been noted for Charophyta (61 % of cases), Myriophyllum and Ceratophyllum, Cu – Charophyta, Isoetes and Lobelia dortmanna, Pb – Isoetes, Charophyta and Potamogeton. The macrophytes within rivers are characterized by the higher ash content and the average content of Mn, Cu and Pb in comparison with the lakes plants. Areas with identified Cu and Pb anomalies in the submerged plants are confined to the central geochemical province of Belarus (the Svisloch river accounts for 67 % of anomalous values of Cu and 33 % of Pb). Anomalous values of Cu have been fixed in the tissues of the Ceratophyllum and Potamogeton, Pb – mostly in Potamogeton. The cluster analysis has distinguished a group of plant species as a part of the following genera: Potamogeton, Myriophyllum, Elodea, Ceratophyllum and Sparganium. The group is characterized by elevated contents of Ti, V, Cr, Mn, Ni, Cu, Zn, Zr, Pb and recommended as indicators of polluting water objects with heavy metals.
Keywords: heavy metals; higher aquatic flora; ecological groups; outliers; spatial patterns; monitoring